The Role of Heparin and Glycocalyx in Blood–Brain Barrier Dysfunction - Yang, Rui; Chen, Mingming; Zheng, Jiayin; Li, Xin; Zhang, Xiaojuan (Frontiers in Immunology, 2021)
The blood-brain barrier (BBB) functions as a dynamic boundary that protects the central nervous system from blood and plays an important role in maintaining the homeostasis of the brain. Dysfunction of the BBB is a pathophysiological characteristic of multiple neurologic diseases. Glycocalyx covers the luminal side of vascular endothelial cells. Damage of glycocalyx leads to disruption of the BBB, while inhibiting glycocalyx degradation maintains BBB integrity. Heparin has been recognized as an anticoagulant and it protects endothelial glycocalyx from destruction. In this review, we summarize the role of glycocalyx in BBB formation and the therapeutic potency of heparin to provide a theoretical basis for the treatment of neurological diseases related to BBB breakdown.